Aplicação das técnicas de microextração μMSPD e BAμE para determinação de alcaloides em matrizes in natura e processadas de tabaco (Nicotiana tabacum L.) por cromatografia líquida acoplada a espectrometria de massas - Santos, Luis Fabrício Santana (2019)
Tobacco is a plant of the genus Nicotiana from the Solanaceae family, whose Nicotiana Tabacum L. is the most cultivated and commercialized species. Despite the wide diversity of chemicals, the alkaloids play an important role in the chemical composition of tobacco due the effects that have made this commodity a worldwide prominence. The indole and β-carboline alkaloids are secondary metabolites formed from the biosynthetic pathway of the amino acid L-tryptophan. These compounds show inhibitory action of the enzyme monoamine oxidase (MAO) that enhances, in smokers, the susceptibility to chemical dependence. However, research also highlights its important effects on the Central Nervous System (CNS), which puts them in a prominent position for studies in different areas of science. In this context, this study presents the development and validation of microextraction analytical methods for determination of N,N-Dimethyltryptamine, harmaline, harmalol, harman, harmine, norharman, tetrahydroharmine and tryptamine alkaloids in natural and processed samples of tobacco and cigarrete smoke by micro-matrix solid-phase dispersion (μMSPD) bar adsorptive microextraction (BAμE), ultra high performance liquid chromatography (UHPLC) and mass spectrometry (MS). The instrumental conditions of analysis were optimized to ensure reliable alkaloid identification and quantification results. The μMSPD procedure was optimized as follows: 0.01 g sample, 0.1 g Discovery DPA 6S adsorbent and elution with 2 mL 1% aqueous formic acid solution. The BAμE procedure was optimized using an extraction device containing the OASIS HLB adsorbent, with extraction step of floating mechanism (3h and 1500 rpm by vortex mechanism) in aqueous solution, and back extraction step by sonication using 100 μL methanol for 5 min. The developed methods were applied to tobacco and cigarette smoke samples, proving to be efficient for the determination of indol and β-carboline alkaloids. The alkaloids harman and norharman were detected in all samples analyzed. For the first time, harmine was identified in tobacco leaf samples.